Knowledge of Neonatal Danger Signs among Postnatal Mothers at Women and New born Hospital - University Teaching Hospitals in Lusaka Zambia. - Chali , Josephine C.; zulu , Mutinke; Ngoma , Catherine (International Journal of Health Sciences, 2024)
Purpose: The awareness and identification of neonatal danger signs by mothers play a significant role in a neonate's survival and future health. The survival of neonates is thought to be increased by providing a clear understanding of neonatal danger signs. This study aimed to assess postnatal mothers' knowledge of neonatal danger signs and associated factors. Methodology: A cross-sectional analytical study design was used to conduct a study at Women and Newborn Hospital UTH in Lusaka Zambia with a total number of 150 participants. Participants recruited in the study included all mothers aged 18 and above seeking care at UTH from day six today twenty-eight after delivery. Data was collected using the validated Neonatal Danger Signs Knowledge and Practices Questionnaire (NDSKQ) tool and SPSS version 26 was used to analyse data. A Binary logistic regression analysis was done to identify factors associated with Neonatal danger signs. Findings: Slightly above half (53%) of the respondents had poor knowledge on neonatal danger signs. Age, marital status, educational level, parity, antenatal care attendance and family support system were associated with knowledge on neonatal danger signs with all p values of less than or equal to 0.05. Younger mothers (18-20 years) (56.5%) were more likely to have poor knowledge compared to older mothers. Married mothers (68%) and those who were divorced or widowed (60%) were more likely to have better knowledge compared to single mothers, mothers with tertiary education (60%) had better knowledge compared to those with none/primary education (58%), mothers with more children (66.7%) were less likely to have poor knowledge compared to those with their first child (50%), mothers who attended antenatal care six times or more (67.1%) had better knowledge compared to those who attended five times or less (53.8%) and mothers with a family support system (75%) were more likely to have good knowledge compared to those without (53%) all the associations were statistically significant. Unique contribution to theory, policy and practice: There is need to focus on training in maternal identification of neonatal danger signs. Personalised education for mothers, considering age and education level, and integrating family involvement and cultural competence into care delivery are crucial. Nursing education should advance through specialized curricula, utilizing advanced simulation training and interdisciplinary collaboration to enhance clinical skills in identification of neonatal danger signs and promote maternal awareness of neonatal dangers signs, ultimately improving neonatal health.